Estimate Expression Levels of LPA Receptor 1, and LPA Receptor 2 Genes Epithelial Ovarian Cancer Cell Lines Using qPCR and Immunocytochemistry Approach - Thaera Fruka; Mustafa Esmaio; Donovan Hiss; Okopi Ekpo; Faghri Februrary (AlQalam Journal of Medical and Applied Sciences, 2025)
Epithelial ovarian carcinoma accounts for the highest number of mortalities among patients with ovarian cancer. However, the molecular mechanisms fundamental to Epithelial Ovarian Cancer (EOC) tumorigenesis are presently ambiguous. In this study, a Real-time–quantitative polymerase Chain Reaction(RT-qPCR) was selected to manipulate Lipoprotein Receptor 1(LPAR1), and Lipoprotein Receptor 2 (LAPR2) gene expression in ovarian cancer cell lines. Immunocytochemical staining was used to examine the expression of LPAR1, 2 in Ovarian Adenocarcinoma W42 (OAW42) and Cystadenocarcinoma Ovary( SKOV3), which are ovarian cancer cell lines, and using Human Ovarian Surface Epithelium Cell (HOSEpiC) as a negative, which was created, from human ovarian surface epithelial cells. The results established that LPAR1, 2 expressions were upregulated in OAW42 and SKOV3 when using the qPCR technique to assist, however, the immunocytochemistry results showed the expression of LPAR1, and LPAR2 in the OAW42 SKOV3and HOSEpiC which is indicated that both of LPAR1 and LPAR2 are not good biomarkers to detect the Epithelial Ovarian Cancer at an early stage. In conclusion, the results of the present study indicate the correlation between LPAR1 and LPAR2 does not serve as biomarkers or diagnostic targets in EOC on the other hand, using qPCR and Immunocytochemistry (ICC) techniques is considered good tools to use. يشكل سرطان المبيض الظهاري أعلى عدد من الوفيات بين مرضى سرطان المبيض. ومع ذلك، فإن الآليات الجزيئية الأساسية لتكوين الورم في سرطان المبيض الظهاري غامضة في الوقت الحالي. في هذه الدراسة، تم اختيار تفاعل البوليميراز المتسلسل الكمي في الوقت الحقيقي للتلاعب بتعبير جين مستقبل البروتين الدهني 1 ومستقبل البروتين الدهني 2 في سلالات خلايا سرطان المبيض. تم استخدام التلوين المناعي الكيميائي لفحص تعبير جين مستقبل البروتين الدهني 1، 2 في سرطان المبيض الغدي وسرطان المبيض الكيسي، وهما سلالات خلايا سرطان المبيض، واستخدام خلايا ظهارة سطح المبيض البشرية كصورة سلبية، والتي تم إنشاؤها، من الخلايا الظهارية سطح المبيض البشرية. أثبتت النتائج أن تعبيرات جين مستقبل البروتين الدهني 1و 2 قد ارتفعت في سرطان المبيض الغدي و وسرطان المبيض الكيسي عند استخدام تقنية البوليميراز المتسلسل الكمي في الوقت الحقيقي للمساعدة، ومع ذلك، أظهرت نتائج المناعة الخلوية التعبير عن جين مستقبل البروتين الدهني و جين مستقبل البروتين الدهني 2في سرطان المبيض الغدي وسرطان المبيض الكيسي و خلايا ظهارة سطح المبيض البشرية مما يشير إلى أن كل من جين مستقبل البروتين الدهني 1و جين مستقبل البروتين الدهني 2ليسا مؤشرين حيويين جيدين للكشف عن سرطان المبيض الظهاري في مرحلة مبكرة. وفي الختام، تشير نتائج الدراسة الحالية إلى أن الارتباط بين جين مستقبل البروتين الدهني 1و جين مستقبل البروتين الدهني 2لا يعمل كمؤشرات حيوية أو أهداف تشخيصية في سرطان المبيض الظهاري من ناحية أخرى، يعتبر استخدام تقنيات تفاعل البوليميراز المتسلسل الكمي في الوقت الحقيقي و الكيمياء المناعية الخلوية كأدوات جيدة للاستخدام